Improving Employee Work Morale through Work Environment and Workload - Sayuti, Bangkit Johan; Suparmi, Suparmi; Musprihadi, Ribut (Untag Business and Accounting Review, 2025)
This study aims to determine the effect of the work environment and workload on employee morale. The population comprises all employees of Tokopedia Pedurungan Semarang, divided into three divisions: seller, buying, and digital, with a sample of 72 respondents. The sampling technique used is proportional stratified random sampling. The data source is primary data, collected using a questionnaire. The data analysis technique employed is multiple linear regression. The hypothesis tests show that both the work environment and the workload have a statistically significant positive effect on employee morale, indicating that improvements in these factors are associated with higher morale. The coefficient of determination is 0.534, indicating that the work environment and workload account for 53.4 percent of the variance in work morale. This study concluded that both the work environment and workload contribute positively to employees' morale. Further research is warranted, particularly regarding other factors influencing work morale.